"With grace under pressure": How critique as signature pedagogy fosters effective music performance. (July 2017) - Hastings, David M
Inspired by seminal writings on Critique as Signature Pedagogy in the Arts and performance as Signature Pedagogy in Music, this article unifies these two concepts into a study of how critique as signature pedagogy in music-performance promotes student learning. This essay seeks to first define the notion of different mindsets as musicians perform and as they practice for performances, and then explores the role of critique in guiding students toward these music-performance ways of thinking and habits of mind. The essay defines four different ways of applying critique (teacher-coach critique, self critique, audience critique, and peer critique) as a key teaching practice or signature pedagogy in the music-performance discipline. Finally, the essay ends with a description of a learning experience that effectively illustrates this pedagogy in a studio class setting.